2017
DOI: 10.1039/c7sc01441d
|View full text |Cite
|
Sign up to set email alerts
|

Emerging plasmonic nanostructures for controlling and enhancing photoluminescence

Abstract: Here, we review recent advances and provide perspectives in photoluminescence modulation and enhancement with plasmonic nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 67 publications
(64 reference statements)
0
91
0
Order By: Relevance
“…The energy is eventually dissipated in the metal (ohmic loss), though it can be emitted by the metal with a very low quantum efficiency. Coupling between dipole emitters and SPs may also modify the emission direction and polarization [51][52][53][54]. The light emission from a quantum emitter can be steered in a specific direction in space by either using simple anisotropic plasmonic nanostructures that exhibit angular and polarization dependent SP resonances or by designing more complex, multicomponent plasmonic nanostructures, such as optical Yagi-Uda nanoantennas [61,62].…”
Section: The Exciton-plasmon Composite System: Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy is eventually dissipated in the metal (ohmic loss), though it can be emitted by the metal with a very low quantum efficiency. Coupling between dipole emitters and SPs may also modify the emission direction and polarization [51][52][53][54]. The light emission from a quantum emitter can be steered in a specific direction in space by either using simple anisotropic plasmonic nanostructures that exhibit angular and polarization dependent SP resonances or by designing more complex, multicomponent plasmonic nanostructures, such as optical Yagi-Uda nanoantennas [61,62].…”
Section: The Exciton-plasmon Composite System: Backgroundmentioning
confidence: 99%
“…The weak coupling regime5.1 Underlying physicsWhen an emitter is weakly coupled to a PC, its PL is modified in multiple ways[51][52][53][54], which may include reshaping of its spectrum and polarization, intensity enhancement or quenching, modulation of radiative and non-radiative…”
mentioning
confidence: 99%
“…To be an efficient fluorescent probe for imaging applications, the thickness of the metallic shell is another critical parameter that significantly impacts on the optical properties (i.e., LSPR and light transmittance) of core–gap–shell nanostructures . For example, tuning the thickness of the Au shell would give rise to a shift in LSPR of the nanostructures.…”
Section: Discussionmentioning
confidence: 99%
“…One remarkable observation is that the signal intensity of the SERS-BG correlates with the signal intensity of the analyte 39,43−45 . Moore et al 43 revealed a relationship of analyte signals and SERS-BG signals of Rhodamine 6G enhanced by colloidal silver via 2D correlation analysis in dependence of the Raman shift. Mahajan et al 39 showed that the relation between the SERS-BG maximum signal intensity and analyte signal intensity is dependent of the SERS substrate plasmon properties, the type of molecule as well as the analyte coverage.…”
Section: Introductionmentioning
confidence: 99%